Application of digital marketing strategies and their impact on startups: A systematic literature review from 2021 to 2024 - Velezmoro López, José Antonio; Córdova Chávez, Diego Vincent; Mego Sotelo, Alina Isabel (LACCEI, 2025)
Startups face various challenges to excel and sustain themselves in such a competitive and changing market. The purpose of this study was to understand the application of digital marketing strategies and their impact on startups. A mixed-method approach and a non-experimental design were used, corresponding to a review without meta-analysis. Inclusion and exclusion criteria using the PRISMA method were used to identify studies focused on digital strategies applied in different contexts between 2021 and 2025, in academic databases such as Scopus, Scielo, and Google Scholar. The results show that the use of social media, such as Facebook and Instagram, represents a key tool for improving brand positioning, increasing web traffic, and strengthening customer relationships. Although countless companies in different sectors have not yet implemented advanced digital strategies, it has been confirmed that the application and management of social media can generate a positive impact on sales, positioning, loyalty, and engagement. The application of digital marketing strategies turns out to be highly positive when used in emerging companies.